Using Text-to-Speech Media to Improve Istima' and Kalam Skills in Arabic Language Learning - Afriani Fajriah; Nabila Mutia Tsani; Dede Mulyaningsih; Khairun Nisa Hasugian (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
This study investigates the effectiveness of Text-to-Speech (TTS) media in enhancing Arabic listening (istima’) and speaking (kalam) skills among grade XI students at Madrasah Aliyah Negeri (MAN) Cimahi. Employing a quasi-experimental design, the research compared student performance in experimental and control groups before and after the integration of TTS media in the learning process. Pre-test results indicated marginally higher average scores in the experimental group compared to the control group. Following the intervention, the experimental group demonstrated significant improvement, particularly in speaking skills, achieving an average score of 85.72, compared to 84.89 in the control group. Conversely, listening skills showed a slight advantage for the control group post-intervention. Statistical analysis confirmed that the use of TTS media significantly enhanced students’ speaking and listening abilities, with a more pronounced effect on speaking proficiency. These findings suggest that TTS media is an effective tool for supporting the development of Arabic language skills, especially in improving oral communication.